The Boxcar Children - Chuba, Daniel; Dippé, Mark A. Z.; Sheen, Martin; Sand, Martin; Simmons, J. K.; Warner, Gertrude Chandler, 1890-1979 (Fort Mill, SC : Phase 4 Films, 2014)
When four orphaned and homeless children come across an abandoned boxcar, they turn it into their home to avoid living with their grandfather, who they've never met.
Originally released as a motion picture in 2014.
Based on the characters created by Gertrude Chandler Warner.
Dolby digital 5.1, anamorphic wide screen 1.77:1.
Voices: Martin Sheen, Jadon Sand, JK Simmons, Joey King, Mackenzie Foy, Zachary Gordon.
MPAA rating: G.
In English or French.
Keywords: Boxcar children (Fictitious characters) -- Drama; Brothers and sisters -- Drama; Orphans -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films; Animated films